Liquid biopsy: miRNA as a potential biomarker in oral cancer. (February 2019) - Mazumder, Sayani; Datta, Shalini; Ray, Jay Gopal; Chaudhuri, Keya; Chatterjee, Raghunath
Highlights: Circulating miRNAs are extremely stable in high pH, temperatures and RNase treatment. Circulating miRNAs in serum, plasma and saliva of oral cancer patient can be used as biomarkers. Population and stage of cancer specific miRNAs need to be identified as biomarkers. Knowledge of prognostic and therapeutic potential of these miRNAs can be used in treatment. Uniformly deregulated circulating miRNAs need to be tested among different populations. Abstract: Oral cancer is one of the leading cancers in South-Asian countries. Despite the easy access of the oral cavity, the detection and five year survival rates of OSCC patients are dismal. Identification of non-invasive biomarkers to determine the progression and recurrence of OSCC could be of immense help to patients. Recent studies on oral cancer suggest the importance of non-invasive biomarker development. Micro-RNAs (miRNAs) are one of the important components of the cell-free nucleic acids available in different body fluids. Here, we have reviewed the current understanding of circulating miRNAs as non-invasive biomarkers in different body fluids of oral cancer patients. A number of circulating miRNAs are found to be common in the body fluids of OSCC patients, while many of these are study specific, the possible sources of this variability could be due to differences in sample processing, assay procedure, clinical stage of the disease, oral habit and environmental factors. The prognostic and therapeutic significance of these circulating miRNAs are suggested by several studies. Mir-371, mir-150, mir-21 and mir-7d were found to be potential prognostic markers, while mir-134, mir-146a, mir-338 and mir-371 were associated with metastases. The prognostic markers, mir-21 and mir-7d were also found to be significantly correlated with resistance to chemotherapy, while mir-375, mir-196 and mir-125b were significantly correlated with sensitivity to radiotherapy. Despite the promising roles of circulating miRNAs, challenges still remain in unravelling the exact regulation of these miRNAs before using them for targeted therapy.